PROJECT TEAMS AS A KEY PLAYER IN IMPLEMENTING CHANGES - Verbovska, Lesya; Фастівський, Георгій Вадимович; Гамуляк, Назар Миколайович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article examines the role of project teams as a key player in implementing changes in the development of a business entity, with an emphasis on team formation, structure, and management in a dynamic environment. Approaches to organizing and forming project teams are analyzed; they are classified according to Davidson Frame (isomorphic, expert, collective, "surgical"), which enables uniting specialists with different competencies to perform roles in transformational processes. A description of the team life cycle is proposed: formation (selection, role assignment), cohesion (development of "team spirit"), active work, restructuring, and dissolution, taking into account challenges such as novelty, risks, and tight deadlines. It is noted that effectiveness is achieved through balancing cultural differences, motivation, and transparent communication, which transforms uncontrolled changes into manageable ones. A detailed description of team roles is provided, based on the theory of Raymond Meredith Belbin. According to it, roles are divided into categories: task-oriented (shapers — dynamic leaders; implementers — practical executors; completer finisher — quality controllers), social (resource investigator — opportunity communicators; coordinator — motivators; teamworker — harmonizers), and intellectual (plant — idea creators; monitor evaluator — analysts; specialist — experts). The analyzed roles ensure synergy, indicating that the human factor (intellect, motivation, ethics) dominates over resources. It is generalized that for objective assessment of competencies and role prioritization, it is necessary to use the Analytic Hierarchy Process (AHP) method by Thomas L. Saati. An algorithm is proposed: construction of a pairwise comparison matrix for roles according to Saati's scale; calculation of weights via geometric mean, with ranking results presented. It is summarized that project teams enhance competitiveness under conditions of change, have greater adaptability to the environment, but require role balance to overcome problems during changes in the team environment. It is proven that the strategic goal of the project groups the team as a social organism, providing priority to leadership and sustainability.